Battery pack bottom guard plate and battery pack and vehicle containing the same
By using solvent-based or solvent-free coatings of specific thickness and surface roughness on the battery pack bottom guard plate, combined with electrophoretic layer protection, the problem of insufficient wear resistance of the battery pack bottom guard plate is solved, and the use of the battery pack is extended Lifespan and improve corrosion resistance.
Patent Information
- Application Number
- CN202410993373.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The wear resistance of the existing battery pack bottom guard plate coating is insufficient, which leads to easy wear during the transmission of the chain or roller of the battery swap station, affecting the service life of the battery pack, especially in the high-frequency battery swap scenarios of NIO second-generation battery swap stations. Under the 15-year warranty requirement is difficult to meet.
Use solvent-based or solvent-free coatings with a thickness of 200μm-900μm and a surface roughness of ≤20μm, combined with materials such as epoxy, polyurea or acrylic to improve the wear resistance of the battery bottom guard plate, and pass the first and second The second electrophoretic layer protects the metal plate and prevents corrosion.
It significantly increases the number of times the battery pack flows in the battery swap station, extends its service life, and further improves the wear resistance and life of the battery pack by isolating the metal plate from the external environment.
Smart Images

Figure CN118554098B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a battery pack bottom guard plate and a battery pack and a vehicle containing the same. Background Art
[0002] In the past two years, the domestic new energy vehicle market has shown a rapid growth trend. With the rapid development of new energy, the energy replenishment system has become an unavoidable problem. At present, there are two ways to replenish energy for pure electric vehicles in China. One is the more common construction of charging piles, and the other is to deploy battery swap stations like NIO. On the one hand, battery swapping has an overwhelming advantage in energy replenishment efficiency, such as being more convenient and faster. On the other hand, due to the unified management of battery swap stations, all users no longer need to worry about battery attenuation and safety issues, and can get a battery check every time they swap batteries.
[0003] At present, the warranty period of power batteries is generally 8 years. Battery companies do not have much economic motivation to extend the service life of batteries after selling batteries or vehicle manufacturers that take the charging and energy replenishment route after selling vehicles. For NIO, which takes the battery replacement and energy replenishment route, if the service life of the battery can be extended, it can bring huge economic benefits. At present, NIO plans to promote 15 years of worry-free battery service and increase the power battery warranty from 8 years to 15 years, which puts more stringent requirements on the battery service life. However, there are few existing technical reports on how to increase the service life of power batteries to 15 years. Summary of the invention
[0004] The applicant found that when the battery pack is replaced and recharged, it needs to be transported and circulated through chains or rollers at the battery swap station. During the transmission process, the bottom protective plate of the battery pack will inevitably come into contact with the chains or rollers, causing friction; if the wear resistance of the coating on the bottom protective plate of the battery pack is poor, it will cause the coating to become thinner or even expose the metal bottom plate, increasing the risk of the metal bottom plate being exposed or even corroded or punctured by external forces, affecting the service life of the battery pack.
[0005] At present, the coating of the bottom guard plate of the battery pack is often made of solvent-based polyvinyl chloride (PVC) coating to achieve the effect of corrosion resistance and stone impact resistance, without considering the wear resistance of the coating. Taking the second-generation battery swap station of NIO as an example, the chains used for battery swap transmission and circulation are distributed in four positions: docking position, cache position, lifting position and battery position. When the battery pack is transferred from one position to another, the chain and the bottom guard plate of the battery pack slide and rub. The existing battery pack with PVC coated bottom guard plate will be worn after 500-800 power swaps at the battery swap station, exposing the anti-corrosion layer underneath, thus affecting the service life of the battery pack. If the service life of the battery pack is to be increased to 15 years, according to the normal frequency of use, the battery pack ideally needs to circulate in the battery swap station 1,500 times without wearing out the bottom guard plate coating.
[0006] To address this problem, the present application provides a battery pack bottom guard plate, which can improve the wear resistance of the battery pack bottom guard plate coating, increase the number of times the battery pack is circulated at a battery swap station, and improve the service life of the battery pack. At the same time, the coating can also serve as a protective layer to effectively isolate the metal plate from the external environment, protecting the metal plate from environmental erosion, thereby improving the life of the battery pack.
[0007] The first aspect of the present application provides a battery pack bottom guard plate, comprising a metal plate and a first electrophoretic layer located on a first surface of the metal plate and a second electrophoretic layer located on a second surface of the metal plate, wherein a coating is provided on a surface of the first electrophoretic layer away from the metal plate, wherein the coating is a solvent-based coating or a solvent-free coating, wherein the thickness of the coating is 200 μm-900 μm, and the surface roughness of the coating is ≤20 μm.
[0008] A second aspect of the present application provides a battery pack, which includes the battery pack bottom guard plate as described in the first aspect, and the coating is arranged on the outer surface of the battery pack.
[0009] A third aspect of the present application provides a vehicle, comprising the battery pack as described in the second aspect, wherein the battery pack is mounted on the bottom of the vehicle.
[0010] The beneficial effects of the present application are as follows: the wear resistance of the battery pack bottom guard plate of the present application is improved through the solvent-based coating or solvent-free coating on the metal plate, so that the battery pack can withstand the continuous scraping and friction caused by the periodic sliding of the transmission chain or roller during the battery replacement process, increasing the number of battery pack circulations in the battery replacement station and improving the service life of the battery pack. At the same time, the solvent-based coating or solvent-free coating can effectively isolate the metal plate from the external environment, protect the metal plate from environmental erosion, and further improve the life of the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a schematic diagram of the structure of the bottom guard plate of the battery pack in Example 1 of the present application;
[0012] Figure 2 It is a schematic diagram of the structure of the bottom protective plate of the battery pack of Examples 2-4 and Comparative Examples 1-2 of the present application.
[0013] In the figure, 1 is a metal plate, 21 is a first electrophoretic layer, 22 is a second electrophoretic layer, 31 is a solvent-free coating, and 32 is a solvent-based coating. DETAILED DESCRIPTION
[0014] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0015] In this application, the terms "upper", "lower", "inner", "outer" and the like indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings, which are only for the convenience of description, and do not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the application. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0016] In this application, unless otherwise clearly specified and limited, the terms "installation", "setting", and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, an indirect connection through an intermediate medium, or the internal connection of two components. For those skilled in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0017] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0018] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0019] 1. Battery pack bottom guard plate
[0020] The first aspect of the present application provides a battery pack bottom guard plate, comprising a metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, wherein the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating being a solvent-based coating or a solvent-free coating, the coating having a thickness of 200μm-900μm, and a surface roughness of ≤20μm. The applicant has found that by matching the specific thickness and specific surface roughness of the solvent-based coating or the solvent-free coating, the wear resistance of the battery pack coating can be improved, and the number of times the battery pack is circulated in the battery swap station can be increased.
[0021] In the present application, "solvent-based coating" refers to a coating formed by curing a solvent-based coating, wherein the solvent-based coating is a coating that is liquid at room temperature and contains a volatile organic solvent as a dispersion medium. During the curing process of the coating, the organic solvent evaporates to form a coating.
[0022] In the present application, "solvent-free coating" refers to a coating formed by curing a solvent-free coating, wherein the solvent-free coating is a coating that is liquid at room temperature and substantially does not contain volatile organic solvents.
[0023] In this application, "wear resistance" refers to the ability of the coating surface to resist wear and tear, which is a kind of material durability. "Wear resistance" means that the coating is not easily worn under high-frequency friction, and the surface will not show phenomena such as thinning and peeling of the skin.
[0024] In this application, "battery swap station circulation times" refers to the number of times a battery pack completes a round trip between the battery compartment and the battery swap platform through the battery transfer and conveying system in the battery swap station. Here, the "battery transfer and conveying system" is used to transfer batteries between the battery swap station platform and the battery compartment, the "battery swap platform" is used to locate and swap batteries for the vehicle, and the "battery compartment" is used to store and charge the battery. Taking the second-generation NIO battery swap station as an example, a battery swap station circulation time refers to a battery pack going back and forth through the cache position, docking position, lifting position and battery compartment in the battery swap station.
[0025] In some embodiments, the thickness of the coating is exemplarily 200μm, 220μm, 250μm, 280μm, 300μm, 320μm, 350μm, 380μm, 400μm, 420μm, 450μm, 480μm, 500μm, 520μm, 550μm, 580μm, 600μm, 650μm, 700μm, 750μm, 800μm, 850μm, 900μm or a range consisting of any two of these values. If the thickness of the coating is too large, the amount of coating material used will increase, resulting in increased costs, and the weight of the entire package will increase, which is not conducive to lightweighting. If the thickness is too small, the mechanical strength and wear resistance of the bottom of the battery pack will be reduced, and the bottom plate of the battery pack will be easily exposed, thereby affecting the safety and reliability of the battery. In some embodiments, the thickness of the coating is 300μm-600μm. In some embodiments, the thickness of the coating is 300 μm-550 μm. In the present application, the thickness of the coating can be regulated by those skilled in the art by adjusting the coating concentration, coating viscosity, coating method, coating speed and other process parameters according to the selected solvent-based or solvent-free coating type.
[0026] In some embodiments, the surface roughness of the coating is exemplarily 20μm, 19μm, 18μm, 17μm, 16μm, 15μm, 14μm, 13μm, 12μm, 11μm, 10μm, 9μm, 8μm or a range consisting of any two of these values. If the surface roughness of the coating is too small, the battery pack is more likely to slip when it circulates in the battery swap station, resulting in reduced circulation efficiency. If the surface roughness is too large, the coating will be more susceptible to external friction, scratches or wear, which is not conducive to improving the wear resistance of the coating. In some embodiments, the surface roughness of the coating is 10μm-20μm. In some embodiments, the surface roughness of the coating is 15μm-20μm. In this application, the surface roughness of the coating can be regulated by those skilled in the art by adjusting the type of solvent-based or solvent-free coating, coating temperature, coating thickness, coating post-treatment methods such as grinding and polishing.
[0027] In some embodiments, the Shore hardness D of the coating is 65-100, exemplarily 65, 68, 70, 72, 75, 78, 80, 82, 85, 88, 90, 92, 95, 98, 100 or a range consisting of any two of these values. The applicant has found that the hardness of the coating is also related to the wear resistance of the coating. The Shore hardness D of the coating within the above range can better improve the wear resistance of the coating and increase the number of battery pack circulations in the battery swap station. If the hardness of the coating is too large, it will wear out the parts of the battery swap station. If the hardness is too small, it will not be conducive to further improving the wear resistance of the battery pack. In some embodiments, the Shore hardness D of the coating is 70-90. In some embodiments, the Shore hardness D of the coating is 70-80.
[0028] In some embodiments, the coating is a solvent-based coating or a solvent-free coating of an epoxy coating, a polyurea coating, or an acrylic coating. In some embodiments, the coating is a solvent-based epoxy coating, a solvent-free polyurea coating, or a solvent-based acrylic coating.
[0029] In a preferred embodiment, the coating is a solvent-based epoxy coating to further improve the wear resistance of the bottom guard plate and increase the service life of the battery pack.
[0030] In some embodiments, the metal plate is a steel plate or an aluminum alloy.
[0031] In some embodiments, the metal plate is a steel plate. Compared with other metal plates, the steel plate has better tensile strength and elongation, can meet the impact resistance requirements, and is beneficial to improving the protection of the battery pack, thereby increasing the service life of the battery.
[0032] In some embodiments, the first electrophoretic layer is an acrylic electrophoretic paint layer, an acrylate electrophoretic paint layer, an epoxy electrophoretic paint layer, a polyurethane electrophoretic paint layer or a polyester electrophoretic paint layer. In a preferred embodiment, the first electrophoretic layer is an epoxy electrophoretic paint layer. As a protective layer, the first electrophoretic layer effectively isolates the metal plate from the external environment of the battery pack and protects the metal plate from environmental erosion, especially when the solvent-based or solvent-free coating is damaged, the metal plate is protected from erosion by the external environment, thereby improving the service life of the battery pack. At the same time, the first electrophoretic layer can increase the adhesion between the solvent-based or solvent-free coating and the metal plate, so that the solvent-based or solvent-free coating is not easy to fall off when it is rubbed or scratched by the outside world.
[0033] In some embodiments, the thickness of the first electrophoretic layer is 25 μm-60 μm, exemplarily 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or a range consisting of any two of these values. In some embodiments, the thickness of the first electrophoretic layer is 25 μm-35 μm.
[0034] In some embodiments, the second electrophoretic layer is an acrylic electrophoretic paint layer, an acrylate electrophoretic paint layer, an epoxy electrophoretic paint layer, a polyurethane electrophoretic paint layer, or a polyester electrophoretic paint layer. In a preferred embodiment, the second electrophoretic layer is an epoxy electrophoretic paint layer. The second electrophoretic layer acts as a protective layer to effectively isolate the metal plate from the internal environment of the battery pack, protect the metal plate from corrosion, and thus improve the service life of the battery pack.
[0035] In some embodiments, the thickness of the second electrophoretic layer is 25 μm-60 μm, exemplarily 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or a range consisting of any two of these values. In some embodiments, the thickness of the second electrophoretic layer is 25 μm-35 μm.
[0036] In some embodiments, the battery pack bottom guard plate includes the metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating is a solvent-based coating or a solvent-free coating of epoxy, polyurea or acrylic, the thickness of the coating is 200μm-900μm, the surface roughness of the coating is ≤20μm, the thickness of the first electrophoretic layer is 25μm-60μm, and the thickness of the second electrophoretic layer is 25μm-60μm.
[0037] In some embodiments, the battery pack bottom guard plate includes the metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating is a solvent-based coating or a solvent-free coating of epoxy, polyurea or acrylic, the thickness of the coating is 300μm-600μm, the surface roughness of the coating is 10μm-20μm, the thickness of the first electrophoretic layer is 25μm-60μm, and the thickness of the second electrophoretic layer is 25μm-60μm.
[0038] In some embodiments, the battery pack bottom guard plate includes the metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating is a solvent-based coating or a solvent-free coating of epoxy, polyurea or acrylic, the thickness of the coating is 200μm-900μm, the surface roughness of the coating is ≤20μm, the Shore hardness D of the coating is 65-100, the thickness of the first electrophoretic layer is 25μm-60μm, and the thickness of the second electrophoretic layer is 25μm-60μm.
[0039] In some embodiments, the battery pack bottom guard plate includes the metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating is a solvent-based coating or a solvent-free coating of epoxy, polyurea or acrylic, the thickness of the coating is 300μm-600μm, the surface roughness of the coating is 10μm-20μm, the Shore hardness D of the coating is 70-90, the thickness of the first electrophoretic layer is 25μm-60μm, and the thickness of the second electrophoretic layer is 25μm-60μm.
[0040] In some embodiments, the battery pack bottom guard plate includes the metal plate and a first electrophoretic layer located on the first surface of the metal plate and a second electrophoretic layer located on the second surface of the metal plate, the first electrophoretic layer is provided with a coating on the surface away from the metal plate, the coating is an epoxy solvent-based coating or a solvent-free coating, the thickness of the coating is 400μm-600μm, the surface roughness of the coating is 10μm-20μm, the Shore hardness D of the coating is 70-80, the thickness of the first electrophoretic layer is 25μm-60μm, and the thickness of the second electrophoretic layer is 25μm-60μm.
[0041] In some embodiments, the thickness of the metal plate is 0.7 mm-1.5 mm, exemplarily 0.7 mm, 0.9 mm, 1.1 mm, 1.3 mm, 1.5 mm or a range consisting of any two of these values. In some embodiments, the thickness of the metal plate is 0.8 mm-1 mm.
[0042] In some embodiments, the thickness of the battery pack bottom guard plate is 0.7 mm-1.5 mm, exemplarily 0.7 mm, 0.9 mm, 1.1 mm, 1.3 mm, 1.5 mm, or a range consisting of any two of these values. In some embodiments, the thickness of the battery pack bottom guard plate is 0.8 mm-1 mm.
[0043] In some embodiments, the compressive pressure of the coating is 10 g / mm 2 -20g / mm 2 , exemplarily 10 g / mm 2 , 12g / mm 2 , 14g / mm 2 , 16g / mm 2 , 18g / mm 2 , 20g / mm 2 Or a range consisting of any two of these values. When the battery pack is replaced, the bottom guard plate needs to withstand the pressure of the entire battery pack, and accordingly the coating on the bottom guard plate also needs to withstand the pressure of the entire battery pack, otherwise it will cause cracking, damage, peeling, etc. of the coating.
[0044] 2. Battery Pack
[0045] The second aspect of the present application provides a battery pack, which includes the battery pack bottom guard plate as described in the first aspect, and the coating is disposed on the outer surface of the battery pack. The solvent-based or solvent-free coating is disposed on the outer surface of the battery pack to improve the battery pack's ability to resist continuous scratching and friction from the external environment, increase the number of battery pack circulations at the battery swap station, and at the same time, as a protective layer, protect the metal plate from erosion by the external environment, thereby increasing the service life of the battery pack.
[0046] In some embodiments, the battery pack includes the battery pack bottom guard plate as described in the first aspect, the coating is disposed on the outer surface of the battery pack, and the second electrophoretic layer is disposed on the inner surface of the battery pack. The second electrophoretic layer is disposed on the inner surface of the battery pack to resist corrosion from the internal environment of the battery pack, such as corrosion from water, acid, alkali, and salt inside the battery pack, thereby further improving the service life of the battery pack.
[0047] 3. Vehicles
[0048] A third aspect of the present application provides a vehicle, comprising a battery pack as described in the second aspect, wherein the battery pack is installed on the vehicle. In some embodiments, the battery pack is installed on the bottom of the vehicle. When the battery pack is installed, the bottom guard plate of the battery pack is arranged toward the ground.
[0049] In some embodiments, the battery pack is mounted on a chassis of the vehicle, and the battery pack bottom guard plate is disposed away from the chassis.
[0050] In some embodiments, the vehicle is a battery-swappable vehicle. In this application, a battery-swappable vehicle generally refers to all vehicles that support a battery-swappable function. In some embodiments, the vehicle has a structure for replacing the battery pack.
[0051] In some embodiments, the vehicle includes, but is not limited to, an electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0052] Example
[0053] In the present application, the methods in the examples, unless otherwise specified, are all conventional methods in the art; the raw materials, materials, and reagents in the examples, unless otherwise specified, are all commercially available conventional raw materials, materials, or reagents.
[0054] Test Method
[0055] 1. Thickness measurement
[0056] Use film thickness meter to measure the thickness of solvent-based coating, solvent-free coating and electrophoretic layer;
[0057] Use a vernier caliper to measure the thickness of the battery pack bottom guard plate.
[0058] 2. Coating hardness measurement
[0059] The Shore D hardness of solvent-based coatings and solvent-free coatings was measured using an LX-D Shore hardness tester.
[0060] 3. Determination of coating surface roughness
[0061] The surface roughness of solvent-based coatings and solvent-free coatings was measured using a 3D profilometer VR-6000 at a magnification of 50 times, and the arithmetic mean height Sa was taken as the surface roughness value. The Z-axis measurement accuracy was 0.4 μm, and the X-axis and Y-axis measurement accuracy was 0.5 μm.
[0062] 4. Coating rotation wear test (Taber test)
[0063] The battery pack bottom guard plate of each embodiment and comparative example was cut into a rectangular sample of 100mm×100mm, and the wear resistance of the solvent-based coating and the solvent-free coating was tested with an abrasion tester at room temperature of 23℃±2℃ and relative humidity of 50%±5%. At least 3 samples of each embodiment and comparative example were prepared for testing, and the test results were averaged. The test method refers to GB / T1768 Determination of wear resistance of paints and varnishes Rotating rubber grinding wheel method;
[0064] The parameters of the grinding wheel and wear machine used in the test simulate the actual situation of the NIO battery swap station. The grinding wheel is a polyurethane grinding wheel, the grinding wheel rotation radius is set to 28.25mm, the grinding wheel speed is set to 72r / min, the grinding wheel thickness is set to 8mm, the single wheel load is set to 2kg, and the Shore hardness D of the grinding wheel is 28-38. Every 1000 revolutions of the grinding wheel, check the wear of the solvent-based coating or solvent-free coating in a standard light source color matching light box. If it is not worn through, use a dry film thickness gauge to measure the film thickness at 3 points of the friction mark and record it, and use an electronic balance to weigh the film weight before continuing the test;
[0065] Stop the test after the grinding wheel runs 30,000 revolutions or the coating is worn through (whichever comes first), and record the reduction in thickness and weight of the solvent-based coating or solvent-free coating, with the thickness accurate to 1μm and the weight accurate to 0.001g. If the coating is not worn through after the grinding wheel runs 30,000 revolutions, record the thickness and weight loss of the coating after running 30,000 revolutions; if the coating is worn through after the grinding wheel runs 5,000 revolutions, record the thickness and weight loss of the coating after running 5,000 revolutions. "Wear through" here refers to the exposure of the electrophoretic layer or metal plate under the solvent-based coating or solvent-free coating.
[0066] Since the above-mentioned wear test simulates the actual situation of a battery swap station, if the coating on the bottom guard plate is not worn through after running 30,000 revolutions, it can be roughly assumed that the coating of the battery pack containing this bottom guard plate is not worn through after 1,500 circulations in the battery swap station, which is equivalent to the service life of the battery pack being increased to 15 years.
[0067] 5. Corrosion resistance test
[0068] Testing the corrosion resistance of the solvent-based coating and the solvent-free coating of the battery pack bottom guard plate of each embodiment and comparative example, including water resistance test, acid resistance test, alkali resistance test and neutral salt spray resistance test;
[0069] Among them, the water resistance test method refers to ASTM D870. The test temperature is 38℃±0.2℃, and the test time is 144h. After 144h of testing, if the coating has no significant discoloration, softening, expansion, blistering, or peeling, and the cross-cut test adhesion is level 0, the coating is considered to have passed the water resistance test, otherwise it is considered to have failed. The acid resistance test and alkali resistance test methods refer to GB / T 9274. The test uses a sulfuric acid (H2SO4) solution with a concentration of 0.05mol / L or a sodium hydroxide (NaOH) solution with a concentration of 0.1mol / L. After 48h of testing, if the coating has no significant discoloration, softening, expansion, blistering, or peeling, and the cross-cut test adhesion is level 0, the coating is considered to have passed the acid resistance test or the alkali resistance test, otherwise it is considered to have failed. The neutral salt spray resistance test method refers to GB / T 10125. After 1000h test, if the coating has no blistering or shedding, the unilateral diffusion distance of the scratch is ≤2mm, and the adhesion of the cross-cut test is level 0, then the coating is considered to have passed the neutral salt spray resistance test, otherwise it is considered to have failed;
[0070] If the coating passes the water resistance test, acid resistance test, alkali resistance test and neutral salt spray resistance test at the same time, it is considered that the coating has passed the corrosion resistance test, otherwise it has failed.
[0071] 6. High and low temperature adhesion test
[0072] The bottom protective plates of the battery packs of the embodiments and comparative examples were stored in an environment of -40°C for 1 hour and then the adhesion of the coating was tested by cross-cutting. If the adhesion was level 0, the coating was considered to have passed the low-temperature adhesion test, otherwise it was considered to have failed.
[0073] The bottom protective plate of the battery pack of each embodiment and comparative example was stored in an environment of 60° C. for 3 hours and then the adhesion of the coating was tested by cross-cutting. If the adhesion was level 0, it was considered that the coating passed the high-temperature adhesion test, otherwise it failed.
[0074] 7. High and low temperature impact resistance test
[0075] The battery pack bottom guard plates of each embodiment and comparative example were cut into rectangular specimens of 150mm×60mm, baked at 80°C for 30min, and then placed for 24h. After that, the specimen plates were placed in a programmable constant temperature and humidity tester at -40°C for 1h and then subjected to impact test. The test conditions were as follows: punch diameter 8mm, groove diameter (15±3)mm, weight 1000g, impact height 50cm. If the coating does not fall to the bottom after the impact test, and there is no crack or peeling, the coating is considered to have passed the low-temperature adhesion test, otherwise it is considered to have failed;
[0076] The battery pack bottom guard plates of each embodiment and comparative example were cut into rectangular specimens of 150 mm × 60 mm, baked at 60°C for 3 hours, and then placed for 24 hours before being subjected to an impact test. The test conditions were as follows: punch diameter 8 mm, groove diameter (15 ± 3) mm, weight 1000 g, impact height 50 cm. If the coating does not fall to the bottom after the impact test, and there is no crack or peeling, the coating is considered to have passed the high temperature adhesion test, otherwise it is considered to have failed.
[0077] 8. High and low temperature flexibility test
[0078] The battery pack bottom guard plates of each embodiment and comparative example were cut into rectangular specimens of 150 mm × 60 mm, baked at 80°C for 30 min, and then placed for 24 h. After that, the specimens were placed in a programmable constant temperature and humidity tester at -40°C for 1 h. After the specimens were taken out, the solvent-based coating or solvent-free coating of the specimens was immediately turned outward, and the specimens were bent 180° along a mandrel with a diameter of 25 mm within 1 second to check for cracks at the bottom. If the coating has no cracks or peeling, it is considered that the coating has passed the low-temperature flexibility test, otherwise it has failed;
[0079] The battery pack bottom guard plates of each embodiment and comparative example were cut into rectangular specimens of 150 mm × 60 mm, baked at 60°C for 30 min, and then left for 24 h. After that, the specimens were bent 180° along a 25 mm diameter mandrel within 1 second with the solvent-based coating or solvent-free coating facing outward to check for cracks at the bottom. If there are no cracks or peeling on the coating, the coating is considered to have passed the high temperature toughness test, otherwise it is considered to have failed.
[0080] Example 1
[0081] The structural schematic diagram of the battery pack bottom guard plate of this embodiment is as follows Figure 1 As shown, it includes a metal plate 1 as a bottom plate, a first electrophoretic layer 21 arranged on the first surface of the metal plate 1, and a second electrophoretic layer 22 arranged on the second surface of the metal plate 1, and a solvent-free coating 31 is arranged on the surface of the first electrophoretic layer 21 away from the metal plate 1. Among them, the metal plate is a steel plate, the first electrophoretic layer is an epoxy electrophoretic paint layer, the second electrophoretic layer is an epoxy electrophoretic paint layer, and the solvent-free coating is a solvent-free polyurea coating. The thickness of the first electrophoretic layer and the second electrophoretic layer, as well as the thickness of the solvent-free coating, Shore hardness D and surface roughness data are detailed in Table 1. The overall thickness of the battery pack bottom guard plate is 0.8mm-1mm.
[0082] When preparing the bottom guard plate of the battery pack, firstly, electrophoresis epoxy is applied on the surface and back of the steel plate, and after baking, the bottom guard plate substrate is obtained, that is, the steel plate with epoxy electrophoretic paint on the first and second surfaces, and the dry film thickness of the first electrophoretic layer and the second electrophoretic layer is 30μm. The back of the bottom guard plate substrate is masked with masking tape, and solvent-free polyurea coating is sprayed on the first surface of the bottom guard plate substrate. After drying, the back masking tape is removed to obtain the bottom guard plate of the battery pack, wherein the thickness of the solvent-free polyurea coating is 300μm, the Shore hardness D is 84.7, and the surface roughness Sa is 18.8μm.
[0083] Example 2
[0084] The structural schematic diagram of the battery pack bottom guard plate of this embodiment is as follows Figure 2 As shown, it includes a metal plate 1 as a bottom plate, a first electrophoretic layer 21 arranged on the first surface of the metal plate 1, and a second electrophoretic layer 22 arranged on the second surface of the metal plate 1, and a solvent-based coating 32 is arranged on the surface of the first electrophoretic layer 21 away from the metal plate 1. Among them, the metal plate is a steel plate, the first electrophoretic layer is an epoxy electrophoretic paint layer, the second electrophoretic layer is an epoxy electrophoretic paint layer, and the solvent-based coating is a solvent-based epoxy coating. The thickness of the first electrophoretic layer and the second electrophoretic layer, as well as the thickness, Shore hardness D and surface roughness data of the solvent-based coating are detailed in Table 1. The overall thickness of the battery pack bottom guard plate is 0.8mm-1mm.
[0085] When preparing the bottom guard plate of the battery pack, first electrophoresis epoxy is applied on the surface and back of the steel plate, and after baking, the bottom guard plate substrate is obtained, that is, the steel plate with epoxy electrophoretic paint on the first and second surfaces, and the dry film thickness of the first electrophoretic layer and the second electrophoretic layer is 30μm. The back of the bottom guard plate substrate is masked with masking tape, and solvent-based epoxy paint is sprayed on the first surface of the bottom guard plate substrate. After drying, the back masking tape is removed to obtain the bottom guard plate of the battery pack, wherein the thickness of the solvent-based epoxy coating is 543μm, the Shore hardness D is 76, and the surface roughness Sa is 16.5μm.
[0086] Example 3
[0087] The structural schematic diagram of the battery pack bottom guard plate of Example 3 is as follows Figure 2 As shown, the overall thickness of the battery pack bottom guard plate is 0.8mm-1mm. The battery pack bottom guard plate of Example 3 is based on Example 2 and adjusts the thickness, Shore hardness D and surface roughness of the solvent-based epoxy coating by changing the spraying process conditions and parameters. The specific adjusted data are shown in Table 1.
[0088] Example 4
[0089] The structural schematic diagram of the battery pack bottom guard plate of this embodiment is as follows Figure 2As shown, it includes a metal plate 1 as a bottom plate, a first electrophoretic layer 21 arranged on the first surface of the metal plate 1, and a second electrophoretic layer 22 arranged on the second surface of the metal plate 1, and a solvent-based coating 31 is arranged on the surface of the first electrophoretic layer 21 away from the metal plate 1. Among them, the metal plate is a steel plate, the first electrophoretic layer is an epoxy electrophoretic paint layer, the second electrophoretic layer is an epoxy electrophoretic paint layer, and the solvent-based coating is a solvent-based acrylic coating. The thickness of the first electrophoretic layer and the second electrophoretic layer, as well as the thickness, Shore hardness D and surface roughness data of the solvent-based coating are detailed in Table 1. The overall thickness of the battery pack bottom guard plate is 0.8mm-1mm.
[0090] When preparing the bottom guard plate of the battery pack, firstly electrophoresis epoxy is applied on the surface and back of the steel plate, and after baking, the bottom guard plate substrate is obtained, that is, the steel plate with epoxy electrophoretic paint on the first and second surfaces, and the dry film thickness of the first electrophoretic layer and the second electrophoretic layer is 30μm. The back of the bottom guard plate substrate is masked with masking tape, and solvent-based acrylic paint is sprayed on the first surface of the bottom guard plate substrate. After drying, the back masking tape is removed to obtain the bottom guard plate of the battery pack, wherein the thickness of the solvent-based acrylic coating is 440μm, the Shore hardness D is 80.6, and the surface roughness Sa is 14.2μm.
[0091] Comparative Example 1
[0092] The structural schematic diagram of the battery pack bottom guard plate of this comparative example is as follows Figure 2 As shown, it includes a metal plate 1 as a bottom plate, a first electrophoretic layer 21 arranged on the first surface of the metal plate 1, and a second electrophoretic layer 22 arranged on the second surface of the metal plate 1, and a solvent-based coating 32 is arranged on the surface of the first electrophoretic layer 21 away from the metal plate 1. Among them, the metal plate is a steel plate, the first electrophoretic layer is an epoxy electrophoretic paint layer, the second electrophoretic layer is an epoxy electrophoretic paint layer, and the solvent-based coating is a solvent-based polyvinyl chloride (PVC) coating. The thickness of the first electrophoretic layer and the second electrophoretic layer, as well as the thickness, Shore hardness D and surface roughness data of the solvent-based coating are detailed in Table 1. The overall thickness of the battery pack bottom guard plate is 0.8mm-1mm.
[0093] When preparing the bottom guard plate of the battery pack, first electrophoresis epoxy is applied on the surface and back of the steel plate, and after baking, the bottom guard plate substrate is obtained, that is, the steel plate with epoxy electrophoretic paint on the first and second surfaces, and the dry film thickness of the first electrophoretic layer and the second electrophoretic layer is 30μm. The back of the bottom guard plate substrate is masked with masking tape, and solvent-based PVC coating is sprayed on the first surface of the bottom guard plate substrate. After drying, the back masking tape is removed to obtain the bottom guard plate of the battery pack, wherein the thickness of the solvent-based PVC coating is 996μm, the Shore hardness D is 56.2, and the surface roughness Sa is 56.4μm.
[0094] Comparative Example 2
[0095] The structural schematic diagram of the battery pack bottom guard plate of Comparative Example 2 is as follows Figure 2 As shown, the overall thickness of the battery pack bottom guard plate is 0.8mm-1mm. The battery pack bottom guard plate of Comparative Example 2 is achieved by changing the spraying process conditions and parameters on the basis of Comparative Example 1 to adjust the thickness, Shore hardness D and surface roughness of the solvent-based PVC coating. The specific adjusted data are shown in Table 1.
[0096] Table 1
[0097]
[0098] Table 2 records the test results of the rotational wear of the bottom guard plate coating of each embodiment and comparative example @ 30000 revolutions. It can be seen that the bottom guard plate coating of Examples 1-4 of the present application has lower wear than the PVC coating of Comparative Examples 1-2, showing excellent wear resistance.
[0099] Table 2
[0100]
[0101] Table 3 records the test results of the anti-corrosion, high and low temperature adhesion, high and low temperature impact resistance and high and low temperature flexibility of the bottom guard plate coating of each embodiment and comparative example. It can be seen that the bottom guard plate coating of Examples 1-4 of the present application and Comparative Examples 1-2 have passed the anti-corrosion test, high and low temperature adhesion test, high and low temperature impact resistance test and high and low temperature flexibility test, and can completely replace the PVC coating.
[0102] Table 3
[0103]
[0104] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A vehicle, characterized in that: A battery pack and a structure for replacing the battery pack, wherein the battery pack is installed on the vehicle, the battery pack includes a battery pack bottom guard plate, the battery pack bottom guard plate includes a metal plate and a first electrophoretic layer located on a first surface of the metal plate and a second electrophoretic layer located on a second surface of the metal plate, a coating is provided on a surface of the first electrophoretic layer away from the metal plate, the coating is a solvent-based coating or a solvent-free coating, the coating is an epoxy coating, the thickness of the epoxy coating is 400 μm-600 μm, and the surface roughness of the epoxy coating is 10 μm-20 μm; The Shore D hardness of the coating is 70-80.
2. The vehicle according to claim 1, characterized in that The thickness of the first electrophoretic layer is 25 μm-60 μm, and / or the thickness of the second electrophoretic layer is 25 μm-60 μm.
3. The vehicle according to claim 1 or 2, wherein the coating is disposed on an outer surface of the battery pack.
4. The vehicle according to claim 3, characterized in that The compressive pressure of the coating is 10g / mm 2 -20g / mm 2 .
